2018
DOI: 10.3233/blc-170147
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Diet-Related Factors, and Bladder Cancer Prognosis: A Systematic Review and Meta-Analysis

Abstract: Background:Urologists are frequently confronted with questions of urinary bladder cancer (UBC) patients about what they can do to improve their prognosis. Unfortunately, it is largely unknown which lifestyle factors can influence prognosis.Objective:To systematically review the available evidence on the association between body mass index (BMI), diet, dietary supplements, and physical activity and UBC prognosis.Methods:We searched PubMed and Embase up to May 2017. We included thirty-one articles reporting on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 53 publications
0
44
2
Order By: Relevance
“…This is in contrast to reports from other cancer sites, which have reported that being overweight or obese may result in functional decline and reduced HRQoL . Despite this finding, there is emerging evidence to suggest an association between BMI and cancer recurrence, and counselling regarding weight loss is recommended .…”
Section: Discussioncontrasting
confidence: 75%
“…This is in contrast to reports from other cancer sites, which have reported that being overweight or obese may result in functional decline and reduced HRQoL . Despite this finding, there is emerging evidence to suggest an association between BMI and cancer recurrence, and counselling regarding weight loss is recommended .…”
Section: Discussioncontrasting
confidence: 75%
“…Although obesity and DM seem to be associated with UBC risk, only few studies are published on their associations with risk of tumour recurrence or progression in NMIBC patients. In a recent meta-analysis based on three historical cohort studies, our group found a pooled hazard ratio (HR) of 1.82 (95% CI: 1.12-2.95) for recurrence and 1.90 (95% CI: 0.93-3.88) for progression in obese versus healthy weight NMIBC patients [9,[19][20][21]. Hwang et al (2011) found increased risks of recurrence and progression for diabetic compared with non-diabetic NMIBC patients [22].…”
Section: Introductionmentioning
confidence: 99%
“…These tables focus mainly on primary tumour characteristics. However, lifestyle factors such as smoking and obesity, as well as diabetes mellitus (DM), may also be relevant in the prognosis of NMIBC [9], and may contribute to more personalized follow-up schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Eighteen studies have assessed the association between body mass index (BMI) and prognosis [7,24,25,30,34,39,59,[65][66][67][68][69][70][71][72][73][74][75]. One study assessed BMI at diagnosis, [24] 13 studies assessed BMI at time of treatment (e.g., transurethral resection of bladder tumor (TURBT), radical cystectomy), [25,30,34,39,59,[65][66][67][68][69][70][71][72] and three studies did not report timing of BMI measurement [73][74][75].…”
Section: Body Mass Indexmentioning
confidence: 99%